2012
DOI: 10.1074/jbc.m111.327866
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Variant for Complex I Reveals a Role in Diabetic Cardiac Remodeling

Abstract: Background: Mitochondrial dysfunction may influence myocardial remodeling in diabetes.Results: Impaired respiratory complex activity and energy depletion without mitochondrial uncoupling was identified in a new conplastic rat model of diabetes. Conclusion: mtDNA mutations are a risk factor for developing myocardial dysfunction in diabetes. Significance: Identifying mtDNA background is important for recognizing patients at risk for heart diseases.Myocardial remodeling and dysfunction are serious complications o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…Mitochondria were isolated from rat heart as described by Sethumadhavan S. et al 45 Briefly, freshly isolated heart tissue was homogenized in modified Chappell Perry medium: 10 mM HEPES, 100 mM KCl, 1 mM EGTA, 5 mM MgSO 4 , 1 mM ATP, and 0.2% BSA, pH 7.4. Homogenates were centrifuged at 700 × g for 15 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondria were isolated from rat heart as described by Sethumadhavan S. et al 45 Briefly, freshly isolated heart tissue was homogenized in modified Chappell Perry medium: 10 mM HEPES, 100 mM KCl, 1 mM EGTA, 5 mM MgSO 4 , 1 mM ATP, and 0.2% BSA, pH 7.4. Homogenates were centrifuged at 700 × g for 15 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, animal studies indicate that mtDNA haplotype can influence longevity, risk for type-2 diabetes, cardiovascular disease, cancer, and fatty liver disease development 1321 . Although cellular studies utilizing animal models of mtDNA variation or immortalized cybrid cell lines have yielded conflicting results in terms of mitochondrial function and ROS production 2224 , to our knowledge no studies have compared mitochondrial function or integrity in normal cells from healthy individuals that represent different mtDNA haplogroups.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies on mitochondrial function in health and disease have provided evidence to associate variants of the mitochondrial genome with pathological states, demonstrating cause and effect relationships that go beyond mere associations is made feasible by characterizing conplastic strains (15,34,38,48,49), which are derived through custom breeding strategies to swap maternally inherited mitochondrial genomes between strains. In the present studies, we found that conplastic rat strains of S and SHR, with virtually identical nuclear genomes but with divergent mitochondrial genomes, demonstrated alterations in cardiac mitochondrial copy numbers and ROS production that were associated with significant differences in ARC and longevity, but not BP.…”
Section: Discussionmentioning
confidence: 99%